FACTOR ANALYSIS AND INDIVIDUAL PROGNOSIS FOR THE PATIENTS WITH FIRST REVEALED ARTERIAL HYPERTENSION - N. E. Gavrilova; V. A. Metelskaya; N. V. Perova; E. B. Yarovaya; S. A. Boytsov; V. P. Mazaev (Российский кардиологический журнал)
Aim. To conduct a comparative research of a variety of angiographic scales with the aim to choose strict and useful scoring system for coronary artery lesion estimation. Material and methods. The cohort of patients is investigated with the age of 25-86 y. (n=502, 70,7% males), who at FSBI "SSRCPM" of the Ministry of Health were underwent coronary arteriography. To evaluate the severity of atherosclerosis by the angiography results the scoring systems Gensisni and SYNTAX were used. Quantitative evaluation of stenoses was done using the software of "General Electric Innova 4100".Results. The groups were formed acorrding to absence, mild or severe coronary atherosclerosis using the Gensini and SYNTAX scores, and also by coronary stenoses prominence. The significant association between all three methods was shown: Spearman correlation coefficient about 0,87. Quantity of points by Gensini and SYNTAX increases according to the quantity of arteries involved. But usage of Gensini score with addition of cut-off points makes more precise the identification of patients with severe coronary arteries lesion.Conclusion. The Gensini scale and the cut-off points provided makes it possible a relevant estimation of coronary arteries lesion and improves the decision whether to revascularize or not.